2010
DOI: 10.1093/eurheartj/ehq026
|View full text |Cite
|
Sign up to set email alerts
|

Physicians' perception of guideline-recommended low-density lipoprotein target values: characteristics of misclassified patients

Abstract: In primary care, about half of high-risk patients receive correct assignment of guideline-recommended LDL targets by their physicians. Perception of correct LDL target values varied largely depending on patients' gender and co-morbid conditions. Poor perception of risk resulted in lower rates of objective LDL target achievement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 37 publications
1
19
0
2
Order By: Relevance
“…These have shown that noncompliance is as high as 70% and occurs across most disciplines and countries [2,[6][7][8][9]. One important aspect that has not been well studied is that of the age of practitioners.…”
Section: Not All Physicians Follow Guidelinesmentioning
confidence: 99%
“…These have shown that noncompliance is as high as 70% and occurs across most disciplines and countries [2,[6][7][8][9]. One important aspect that has not been well studied is that of the age of practitioners.…”
Section: Not All Physicians Follow Guidelinesmentioning
confidence: 99%
“…First, physicians may underestimate the individual risk to their patient. Sager et al19 used logistic regression to analyze whether 907 primary care physicians utilized risk factors and comorbidities appropriately for the assignment of correct LDL-C target values. They found that overall, physicians estimated recommended LDL-C target values correctly in only about half of their 25,000 patients (55.1% of male vs 49.1% of female patients); poor perception of CV risk resulted in lower rates of objective LDL-C target achievement.…”
Section: Discussionmentioning
confidence: 99%
“…European guidelines were first published in 1994 167 and thereafter updated about every four years 3,130,168,169 In primary prevention, the proportion of high-risk individuals with elevated blood lipids treated with lipid-lowering drugs varies widely between countries, from about half to three quarters 8,20,[178][179][180][181] . However, less than half of the treated patients reach the total cholesterol reduction recommended by the guidelines [182][183][184] , 28% in Italy, and from 29% to 48% in Sweden 8,185 . Suboptimal treatment is associated with less reduction of cardiac events 186 .…”
Section: Guidelines On Lipid-lowering Treatmentmentioning
confidence: 98%
“…An international European study showed that the incidence rate of cardiovascular events during three years of observation was more than double in individuals who did not reach the LDL cholesterol reduction target compared to those at target 185 . The presence of co-morbidities and also being female seem to reduce appropriate lipid-lowering treatment 23,182 . Conversely, an overuse of statins has been documented in low-risk individuals with low expected benefits 19,20 .…”
Section: Guidelines On Lipid-lowering Treatmentmentioning
confidence: 99%